Inclusão de alunos com deficiência: um estudo de caso no contexto universitário de uma IES pública no Estado do Paraná. - Pin, Aline Keryn (2014)
The Brazilian university has, in recent years, promoted the access of students with disabilities for a professional academic training. However, how have the relations between teachers / coordinators and included students been established at the university, in order to guarantee a process of inclusion and quality career training? The objective of this study is to investigate the pedagogical and institutional conditions of educational inclusion of students with disabilities in higher education and understand how; they are institutionally organized in public HEIs, the support of graduate courses to teachers and students on the teaching and learning process. A case study was performed on the topic of educational inclusion, it was done in the locus campus of the Universidade Estadual do Oeste do Paraná - UNIOESTE in Cascavel / PR. Sixteen (16) faculty coordinators of undergraduate programs and four (4) students with disabilities (registered and graduates) were interviewed. The dissertation text structure discusses about the Brazilian university genesis and how the process of inclusion was inserted historically at this education level. We analyzed university teaching from the perspective of inclusive education, aiming to understand the diversity in the classroom and the need for teachers to expand their knowledge about the inclusion process. The study showed that the inclusion process at the university includes not only teachers training but also issues regarding institutional commitment, not only for the access of the disabled student, but primarily regarding the conditions of permanence of this student in university.